Optimization of Audit Tool Linked Archive System (ATLAS) on Risk Base Audit - Endang Kusmana; Perdhiansyah; Risti Rahmaniar (Politeknik Negeri Madiun, 2024)
This article discusses the implementation of Project Based Learning (PBL) as a risk-based audit learning model utilizing the Audit Tool Linked Archive System (ATLAS) application. PBL is an effective approach to enhance student engagement and understanding in the audit process, particularly concerning the risks encountered in modern audit practices. By using ATLAS, students can learn independently and purposefully, leveraging technology to access relevant information and data. This study also examines how this learning model can improve students' competencies in the field of auditing and prepare them to face challenges in the workforce. This study uses a qualitative approach with a case study at the Accounting Department of Pontianak State Polytechnic, involving 3rd semester students who were divided into groups for an audit project. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that PBL and ATLAS significantly improved students' understanding of RBA and practical audit skills, with students reporting higher engagement and motivation. Recommendations include the integration of technology into the curriculum and training in the use of applications. The findings conclude that technology-supported PBL such as ATLAS is effective in preparing students for the challenges of the modern workplace.